ANALISIS DAMPAK PENGGUNAAN INTERNET PADA PENDAPATAN PEKERJA SEKTOR INFORMAL DI PERDESAAN DAN PERKOTAAN INDONESIA - Imam Agus Faisal; Hadi Rahadian (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2023)
This study aims to analyze the impact of internet usage on the income of informal workers in Indonesia's urban and rural area. The data used in this study is secondary data, sourced from August 2021 SAKERNAS data. This study uses Propensity Score Matching (PSM) to analyze the main objective. The result of this study shows that informal workers in urban area has more benefits than informal workers in rural area. Meanwhile the internet usage in urban and rural area are not optimal. This study implies that internet usage has worsen the income gap between urban and rural area. Therefore, the government should widen the internet access in all over area, particularly the rural area. Thus, it should provide training or education for informal workers in rural area about awareness of the importance of internet.